Forced online experiment and its acceptance among the University students during pandemic in Pakistan. Issue 3 (4th November 2021) - Abdullah, Iqra; Parveen, Shazia; Haq, Saif Ul
Abstract : Purpose: This study aims to assess the acceptability of online classes among university students of Pakistan through the extension of the unified theory of acceptance and use of technology (UTAUT) model. Design/methodology/approach: This study follows a quantitative research approach and data were collected from 662 university students of 10 different universities of Pakistan through a self-administrative Web survey. Structural equation modeling through SmartPLS was used to analyze the data. Findings: Findings of the research show that performance expectancy, effort expectancy, social influence and facilitating conditions play a significant role in developing the intention to adopt online classes. Furthermore, facilitating conditions and intention to adopt online classes have further resulted in frequent use behavior. The authors also investigated the moderating role effect of active learning in relationship behavioral intention and use behavior. Findings show that active learning is an important component of online classes that interacts with the behavioral intention to develop the behavior of attending the online mode of learning by students. However, no significant moderation of uncertainty was found in the relationship between four components of acceptance of technology and behavioral intention to adopt the technology. Originality/value: The authors have extended the UTUAT model by establishing the relationship between facilitating conditions and behavioral intention that supports e-learning. Furthermore, this study tests the moderating role of uncertainty and active learning on the UTUAT model.